1971
DOI: 10.1679/aohc1950.33.357
|View full text |Cite
|
Sign up to set email alerts
|

Ultrastructural Change in the Parathyroid Gland of the Phosphate Treated Newt, <i>Triturus pyrrhogaster</i> (Boié)

Abstract: Summary. The newt parathyroid gland in natural hibernation and in hyperfunctional conditions induced by the intraperitoneal injection of phosphate was electron-microscopically studied. The average numbers of mitochondria, Golgi apparatus, large homogeneously dense bodies, large heterogeneously dense bodies, vacuolar bodies and lipofuscin-like thyroid glands of the phosphate treated and hibernating (control) newts. The parenchymal cells of the newt parathyroid gland were classified into basal cells and suprabas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

1972
1972
1998
1998

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 30 publications
2
8
0
Order By: Relevance
“…These changes in the experimental mice are thought to be in duced by stimulating the secretory process in most chief cells. These results are fairly con sistent with the observations which demon strate the increase in functional activity of the parathyroid gland [Melson, 1966;Capen and Rowland, 1968;Fetter and Capen, 1970;Yousliak and Capen, 1970;Furuta, 1971;Isono et al, 1971;Altendhr, 1972;Fujii and Isono, 1972;Isono and Shoumura, 1973;Anderson and Capen, 1976 ;Chan, 1977;Isono eta!., I976a,b;Takai, 1976;Coleman and Silbermann, 1978].…”
Section: Discussionsupporting
confidence: 84%
“…These changes in the experimental mice are thought to be in duced by stimulating the secretory process in most chief cells. These results are fairly con sistent with the observations which demon strate the increase in functional activity of the parathyroid gland [Melson, 1966;Capen and Rowland, 1968;Fetter and Capen, 1970;Yousliak and Capen, 1970;Furuta, 1971;Isono et al, 1971;Altendhr, 1972;Fujii and Isono, 1972;Isono and Shoumura, 1973;Anderson and Capen, 1976 ;Chan, 1977;Isono eta!., I976a,b;Takai, 1976;Coleman and Silbermann, 1978].…”
Section: Discussionsupporting
confidence: 84%
“…Furthermore, in the parathyroid gland of the rat within 3 h of phosphate treatment, the surface area of the Golgi com plex and secretory granules is decreased, but after 3 h their surface area is increased, and after 12 h the surface area of the cisternae of the granular endoplasmic reticulum is also increased [4], In the present study, in the parathyroid glands of the P group, cisternae of the granular endoplas mic reticulum were significantly increased and the Golgi complexes appeared to be increased as compared to those of the control group. These results are essentially similar to previous observations showing an increase in function of the parathyroid glands of phosphate-treated animals [1][2][3], Therefore, it is suggested that the synthesis and release of secretory granules may be markedly stimulated in the para thyroid glands of the P-5G group.…”
Section: Discussionsupporting
confidence: 92%
“…These cells have been suggested to play a role as supporting cells (Isono et al, 1971(Isono et al, , 1990Setoguti et al, 1970a).…”
Section: Urodelamentioning
confidence: 99%
“…Parathyroid hormone-induced hypercalcemia in Triturus pyrrhogaster led to a hypofunctional state of suprabasal cells as exhibited by transformed secretory granules into vacuolar bodies through lysosomal type heterogenously dense bodies or some of them through the vesicular type (Isono and Shoumura-Sakurai, 1973). Hyperfunctional conditions have been induced in the parathyroid glands of Triturus pyrrhogaster after injection of phosphate (Isono et al, 1971) or EDTA , resulting in an increase of RER, Golgi complex, large homogenous dense bodies, and lipofuscin-like bodies and a decrease in the number of glycogen granules and vacuolar bodies in the suprabasal cells. The number of mitochondria1 profiles hardly varied as compared to controls.…”
Section: Experimental Studiesmentioning
confidence: 99%